(untitled) - Spatz, Chris (Australia, 2010)
Includes bibliographical references (p. 473-479) and index.; This book is a textbook for a one-term statistics course in the social or behavioral sciences, education, or the allied health/nursing field. Its focus is conceptualization, understanding, and interpretation, rather than computation. Although designed to be comprehensible and complete for students who take only one statistics courses, it includes many elements that prepare students for additional statistics courses
Keywords: Statistics -- Textbooks.; Thống kế -- Giáo trình